Super‐mini percutaneous nephrolithotomy (SMP) vs retrograde intrarenal surgery for the treatment of 1–2 cm lower‐pole renal calculi: an international multicentre randomised controlled trial. (26th July 2018) - Zeng, Guohua; Zhang, Tao; Agrawal, Madhu; He, Xiang; Zhang, Wei; Xiao, Kefeng; Li, Hulin; Li, Xuedong; Xu, Changbao; Yang, Sixing; de la Rosette, Jean J.; Fan, Junhong; et al.
Abstract : Objectives: To compare the safety and effectiveness of super‐mini‐percutaneous nephrolithotomy (SMP) and retrograde intrarenal surgery (RIRS) for the treatment of 1–2 cm lower‐pole renal calculi (LPC). Patients and Methods: An international multicentre, prospective, randomised, unblinded controlled study was conducted at 10 academic medical centres in China, India, and Turkey, between August 2015 and June 2017. In all, 160 consecutive patients with 1–2 cm LPC were randomised to receive SMP or RIRS. The primary endpoint was stone‐free rate (SFR). Stone‐free status was defined as no residual fragments of ≥0.3 cm on plain abdominal radiograph of the kidneys, ureters and bladder, and ultrasonography at 1‐day and on computed tomography at 3‐months after operation. Secondary endpoints included blood loss, operating time, postoperative pain scores, auxiliary procedures, complications, and hospital stay. Postoperative follow‐up was scheduled at 3 months. Analysis was by intention‐to‐treat. The trial was registered athttp://clinicaltrials.gov/ (NCT02519634). Results: The two groups had similar baseline characteristics. The mean (sd ) stone diameters were comparable between the groups, at 1.50 (0.29) cm for the SMP group vs 1.43 (0.34) cm for the RIRS group ( P = 0.214). SMP achieved a significantly better 1‐day and 3‐month SFR than RIRS (1‐day SFR 91.2% vs 71.2%, P = 0.001; 3‐months SFR 93.8% vs 82.5%, P = 0.028). The auxiliary procedure rate was lower in the SMP group. RIRS was found to be superior with lower haemoglobin drop and less postoperative pain. Blood transfusion was not required in either group. There was no significant difference in operating time, hospital stay, and complication rates, between the groups. Conclusions: SMP was more effective than RIRS for treating 1–2 cm LPC in terms of a better SFR and lesser auxiliary procedure rate. The complications and hospital stay were comparable. RIRS has the advantage of less postoperative pain.